Book Review: Medical anthropology at the intersections: histories, activisms, and futures - Stellmach, D (Taylor and Francis (Routledge), 2015)
Overall, given the diverse material, most readers – those not focused on interdis-ciplinary anthropology as a subject – might not attempt a cover-to-cover reading.Researchers of specific topics, or the book’s three sub-headings – histories, acti-visms, futures – should examine the book. It is a solid addition to medical anthro-pology, interdisciplinary by nature.